The Correlation Between Person Deixis and Social Class in Singaraja Society - Vina Widiadnya Putri, I Gusti Ayu; Wahyu Nugraha Putra, I Gusti Bagus; Nova Winarta, Ida Bagus Gde (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This study aims to analyze the correlation between person deixis and social class in Singaraja community. The people of the city of Singaraja use a unique language in their daily communication. Person deixis in communication used in Singaraja uses animal names as personal pronouns. The relationship between social class and person deixis pronouns is interesting to be analysed. This study uses deixis theory and the relationship between deixis and social class from Levinson (1983). He argued that social deixis is related to the aspect of sentences reflecting or establishing the social situation when the speech event occurs which means social deixis is also a deictic expression to distinguish speaker's social, Levinson (1983). This research is qualitative descriptive research. Data was collected by recording and observation techniques from the communication of the Singaraja people and their relationship with the social class of society. The results of this study found that person deixis is used in daily conversations in the Singaraja community such as first person singular, second person singular and possessive pronouns. The research findings state that the type of deixis used is related to the dimensions of the speaker's social class. The social class in question is the difference in class in society